Oxidative Stress and Inflammation in Retinal Degeneration - Ravirajsinh N. Jadeja; Pamela M. Martin (Antioxidants, 2021)
Inflammation and oxidative stress play prominent roles in the pathogenesis of many degenerative diseases of the retina, such as age-related macular degeneration (AMD), diabetic retinopathy (DR), retinal vein occlusion, and retinitis pigmentosa [...]